The association between corporate culture and ESG performance: Insights from Russian companies - Irina N. Tkachenko; Elena N. Tumilevich (Управленец)
Amid globalization and increasing demands for social responsibility, companies are facing the challenge of integrating ESG (environmental, social, and governance) principles into their corporate culture. Their implementation can significantly influence the sustainable development and competitiveness of Russian business. The study aims to examine the association between corporate culture and ESG performance of Russian companies. The theoretical framework combines the theory of corporate governance, as well as the concepts of social responsibility, sustainable development, and ESG. Correlation and regression analysis, content analysis, survey and case study methods are applied. The evidence base was formed by data from 37 companies included in the RAEX ESG Ranking as of 2024. The companies with a strong corporate culture were found to have higher ESG performance. A corporate culture with values borrowed from the Denison Model contributes to more effective implementation of ESG policies, with adaptability being the most significant trait. This, in turn, has a positive impact on the reputation and financial performance of the companies. The research findings add to the understanding of the importance of integrating corporate culture and sustainability principles. The proposed recommendations will be useful for the management of companies seeking to improve ESG performance.